NaIO4/LiBr-Mediated direct conversion of benzylic alcohols and aromatic aldehydes to aromatic esters - Shaikh, Tanveer Mohammad Ali; Emmanuvel, Lourdusamy; Sudalai, Arumugam (Synthetic Communications, 2007)
Aromatic aldehydes or benzylic alcohols are directly converted to the corresponding aromatic esters in high yields on treatment with methanol or ethanol mediated by sodium metaperiodate (NaIO4)/LiBr in an acidic medium.
Keywords: aromatic ester; benazaldehyde; Benzyl alcohol; Lithium bromide; Sodium metaperiodate

NaIO4/LiBr-mediated aziridination of olefins using chloramine-T - Karabal, Pratibha U.; Chouthaiwale, Pandurang V.; Shaikh, Tanveer M.; Suryavanshi, Gurunath; Sudalai, Arumugam (Tetrahedron Letters, 2010)
A new milder protocol for aziridination of a variety of olefins has been described. The process employs catalytic amount of sodium metaperiodate (NaIO4) as an oxidant and LiBr and chloramine-T as the bromine and nitrogen sources, respectively. Interestingly, the formation of aziridine products in all the cases studied takes place presumably through a process of 1,2-aminobromination of alkenes. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Aziridination; Chloramine-T; Lithium bromide; Olefin; Sodium metaperiodate